Development of the beliefs and language awareness of content subject teachers in CLIL: does professional development help? - Lo, Yuen Yi (International journal of bilingual education and bilingualism, 2019)
In Content and Language Integrated Learning (CLIL) programmes, students are expected to master content knowledge and language simultaneously. The worldwide popularity of this kind of programme has called for professional development, particularly for content subject teachers who have to shoulder some responsibilities of language teaching in CLIL. There have been several frameworks or proposals for professional development of CLIL teachers. Yet, empirical studies investigating the effectiveness of CLIL professional development programmes remain scarce. This gap is particularly important, since the relationship between professional development and teacher change is complicated and there are various factors affecting whether and how teacher would change. This study implemented a 6-month professional development programme for a group of content subject teachers in CLIL in Hong Kong. With data gathered with questionnaires, interviews, lesson observations and post-lesson reflections, this paper reports the trajectory of three case teachers who seemed to experience different degrees of changes in beliefs and language awareness. These differences could be explained by the influence of such factors as school context, learning experience and subject discipline. This study yields important implications for teacher education in CLIL and teacher change.